The Influence of Service Quality, Perceived Value, and CRM on Customer Loyalty in Indonesia’s Oil and Chemical Freight Shipping Industry - Poeti Surya Safira Adhelia; Triza Mudita (Journal La Sociale, 2026)
Ensuring customer loyalty in Indonesia’s oil and chemical freight shipping sector remains challenging despite substantial investment in operational improvement and digital technology. In this high risk logistics environment, where compliance, reliability, and safety are essential, customer loyalty is not shaped by service performance alone. This study examines the effects of service quality, perceived value, and Customer Relationship Management on customer loyalty, with customer satisfaction positioned as a mediating variable. Grounded in SERVQUAL, perceived value theory, and relationship marketing, the study adopts a quantitative explanatory approach. Data were collected from 200 corporate clients of PT PCS Internasional and analyzed using Partial Least Squares Structural Equation Modeling. The findings show that service quality significantly improves perceived value but does not directly influence customer satisfaction. This indicates that customers first interpret service performance through the value they receive before forming satisfaction judgments. Perceived value and CRM both have significant positive effects on satisfaction, while satisfaction emerges as the strongest predictor of customer loyalty with a path coefficient of 0.837. Mediation analysis further reveals that loyalty is formed mainly through indirect pathways, especially through the relationship between CRM, satisfaction, and loyalty. The model demonstrates strong predictive power, explaining 94.5 percent of the variance in loyalty. These findings suggest that operational excellence alone is not sufficient to secure long term loyalty. Companies must also strengthen digital CRM, transparent communication, and value delivery. This study contributes to the literature by testing an integrated loyalty model in Indonesia’s hazardous shipping industry, a context that remains rarely explored empirically.